AN ASIAN ECCLESIOLOGY GUIDED BY THE SPIRIT OF VATICAN II: Vision of the Asian Church Based on FABC Documents - Alangaram, A (Asian Horizons, 2012)
The Vatican has renewed and strengthened the universal Church. During the Council there was a Copernican revolution in her understanding of other world religions and other churches in the world. The council opened the eyes of the global Church to understand and identify herself with the poor, the suffering and the people of working classes. She proclaimed her faith conviction that in serving the poor and marginalized she can serve her Master and Lord Jesus Christ more authentically.